Responsible research and innovation meets multispecies studies: why RRI needs to be a more-than-human exercise. Issue 2 (4th May 2021) - Szymanski, Erika Amethyst; Smith, Robert D. J.; Calvert, Jane
ABSTRACT: We offer an argument for why responsible research and innovation should be in conversation with multispecies studies. We suggest that RRI can learn from multispecies studies to expand definitions of stakeholders and responsibilities, thereby including other creatures in conversations and frameworks where they are currently missing. In addition, the RRI community might benefit from exploring conceptual overlaps between RRI and multispecies studies literatures. For example, concepts germane to RRI – notably, care and relationality – have been particularly well-developed with respect to how they oblige mutually responsive relationships. Consequently, connecting these two areas of theory and practice should nuance discussions about responsibility as an individual versus a collective endeavor and about the relationship between RRI and knowledge production.